No evidence of leukaemia (NEL) as a response criteria in paediatric AML: a multicentre analysisResearch in context - Evangelia Antoniou; Annika Puschnig; Naghmeh Niktoreh; Lina Marie Hoffmeister; Markus Schneider; Carolin Augsburg; Christel Katerkamp; Denise Kondryn; Tabea Ziedrich; Jan-Henning Klusmann; Michael Dworzak; Ursula Creutzig; et al. (EClinicalMedicine)
Summary: Background: In AML, the assessment of response is one of the most important prognostic markers and is crucial for assessing clinical trials. Remission criteria for AML defined by Cheson et al. has remained virtually unchanged over the last two decades. Here we revised response criteria and provide a more precise standard for evaluating treatment outcomes in paediatric AML. Methods: A multicentre analysis of real-time data of 1094 paediatric patients diagnosed between 2004 and 2021 within the AML-BFM study group was conducted, categorising them into two alternative response groups “evidence of leukaemia” (EL, ≥5% blasts) and “no evidence of leukaemia” (NEL, <5% blasts) and comparing those with the previous CR versus no-CR classification across three different treatment timepoints. Findings: The survival of patients newly classified as NEL was comparable to that of patients with CR. The revised NEL/EL comparison showed better predictive power in terms of survival than the former CR/no-CR classification. The poorest outcome at the end of induction (EOI) was noticed in patients with EL, which could be improved by HSCT. Stratification by NEL/EL revealed the highest independent predictive effect on overall and event-free survival. The integration of measurable residual disease monitoring using reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) further improved the predictive power of the revised definition. Interpretation: By simplifying the response criteria for morphological assessment of blast persistence (NEL/EL), we provide an improved and more precise definition of response for paediatric AML, which presents a new milestone with a high prognostic impact in daily clinical practice and in interpreting clinical trials. Funding: Deutsche Krebshilfe e.V., University of Duisburg-Essen.